KOMPETENSI PAEDAGOGIK CALON GURU PENDIDIKAN AGAMA ISLAM (Studi Tentang Kompetensi Paedagogik Mahasiswa Jurusan Tarbiyah Program Studi Pendidikan Agama Islam STAIN Pamekasan Tahun akademik 2016) - Mushollin Mushollin (Research Institute and Community Engagement of IAIN MADURA, 2017)
This research is focused on a few things here, How the ability level of the students of Islamic Education Department in planning learning of Islamic Education or Pendidikan Agama Islam (PAI) is?, How the level of ability of the Students of PAI in the understanding of learners in the learning PAI is? How the level in the mastery of students in managing the material ajarPAI is? How the skill level of the students in implementing the approach /strategy of learning is? How the level of skill of students in utilizing resources and media of learning is?, How the skill level of the college students in involving students in teaching learning process is? How the skill level of the student in carrying out the evaluation of learning? This research is a descriptive research. sampling technique using proportional random sampling. Data collection methods used is questionnaire.The validity used was the validity of the content and to determine the reliability using Cronbach Alpha formula. Data analysis that used is descriptive quantitative with percentage.The results of this study showed that the general competence paedagogik student PAI STAIN Pamekasan semester 6 academic year 2016. Of some of the indicators there has been no showing the highest numbers in the scale of Linkert. From some aspects it looks that (1) in ability to plan learning PAI. (2) the Competence of the PAI students in understanding the learners do to prepare physically such as setting up equipment and checking the presence of students in the learning process.And there are only a few students who do pre-learning by preparing students for psychic. (3) the student's Competence in managing the teaching materials look when doing appersepsi at the beginning of learning, the ability in mastering teaching materials, the ability to associate the teaching materials with other relevant knowledge, the ability to notice the material clearly in accordance with the hierarchy, as well as the ability in linking the striker with the reality of life. On these capabilities, yet there are students who are able to reach the maximum level on a scale of linkert, (4) the Ability in implementing the approach and strategies of learning can be seen from the ability of students on teaching practice in terms of implementing the learning in accordance with the competencies to be achieved, implementing the learning coherently in accordance with the sintax, mastery class, the implementation of learning that is konstektual, the implementation of learning that cultivate the habit of positive, carry out learning in accordance with the allocation of time planned. On the indicator of the ability of ability have not shown the maximum results in the these aspects, (5) the Ability to utilize learning resources and teaching media can view of the ability in using the media y effectively and efficiently, the ability to produce messages of interest from the media, as well as the ability to engage students in the utilization of media. From the aspect these aspects have yet to show optimal results, the average ability students only at the level of 4 on a scale of Linkert, (6) aspects of the ability to evaluate students is very weak. Even the majority of students do not carry out the final assessment and also the process.